Ylioppilaita: Kuvaus pohjalaisista ylioppilaista Turun Yliopistossa - Finne, Jalmari, 1874-1938 (Salt Lake City, UT : Project Gutenberg, 2017)
"Ylioppilaita: Kuvaus pohjalaisista ylioppilaista Turun Yliopistossa" by Jalmari Finne is a historical narrative written in the early 20th century. The work centers around students from Pohjanmaa (Ostrobothnia) as they gather in a tavern in Turku to celebrate Epiphany after their Christmas break. The book likely explores themes of youth camaraderie, cultural identity, and the experiences of university life in Finland during the 17th century. The opening of the narrative immerses the reader in the lively atmosphere of a tavern run by Andres Merthen during the year 1655. As students arrive to celebrate the end of their holiday, they indulge in drink and camaraderie, vividly portrayed through their lively banter and interactions. The reader is introduced to a group of students, each with distinctive traits, sharing stories and exchanges filled with humor and rivalry. The setting establishes the cultural backdrop of the time while hinting at deeper social dynamics, illustrated further by their interactions with the tavern keeper and a female character, Taava, who plays a significant role in navigating the students' youthful exuberance. (This is an automatically generated summary.)
Release date is 2017-12-31
E-text prepared by Jari Koivisto
Keywords: Finnish fiction -- 20th century